The Influence of Non-Monetary Rewards on Enhancing Employees’ Performance - K.C., Harendra (The Management Review, 2025)
Non-Monetary rewards are prizes or perks given to workers that do not include direct money remuneration. These incentives inspire workers, increase job satisfaction, and boost performance. As a result, nonmonetary incentives play an important role in improving employee performance. The study's objectives are to examine the impact of non-monetary rewards on employee performance in commercial banks in Karnali Province, specifically how flexible work arrangements, employee recognition, career development opportunities, and job promotions affect employee performance. This study used a structured survey to obtain primary data from 335 workers at several commercial banks in Karnali Province. Participants were selected using convenience sampling, and the data were analyzed using descriptive and inferential statistical techniques to uncover patterns and correlations between non-monetary incentives and employee performance. The results show a favorable and substantial association between employee performance and aspects including flexible work arrangements, career development chances, and job promotions. On the other hand, employee recognition was shown to have a modest influence on performance, demonstrating that the efficiency of various non-monetary incentives differs. The research shows that non-monetary incentives, notably flexible work arrangements, career development opportunities, and job promotions, majorly impact employee performance in the commercial banking industry. Employee recognition, although beneficial, has a less noticeable impact. These results have practical implications for bank managers and HR experts, emphasizing the necessity of developing reward systems that prioritize meaningful nonmonetary incentives. Commercial banks may promote employee engagement, increase productivity, minimize attrition, and support long-term organizational success by emphasizing flexibility, professional development, and progression possibilities.